ANALISIS KESESUAIAN LAHAN BUDIDAYA RUMPUT LAUT (KAPPAPHYCUS ALVAREZII) DI TELUK BIMA, KABUPATEN BIMA, NUSA TENGGARA BARAT - Nurlina Nurlina; Jayadi Jayadi; Abdul Rauf (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2024)
The objectives of this study are 1) Identifying the suitability of seaweed cultivation land, 2) Estimating the carrying capacity of aquatic ecological space, 3) Developing strategies for seaweed cultivation in the coastal area of Bima Bay. The methods used are: spatial data analysis with the Geogerafis Information System method, SWOT analysis to determine the development strategy of seaweed cultivation areas. The results of this study are 1) The Bima Bay Coastal Area has land potential for seaweed cultivation with a very suitable category of ± of 2,188.9 ha, and a suitable ± of 2,512.69 ha. 2) The Bima Bay Coastal Area has a land carrying capacity to support the development of seaweed cultivation with an area of ± 1,410.26 ha with a recommended number of cultivation units of ±11,752 units. 3) Determined 8 best strategies for the development of seaweed cultivation business in the waters of Bima Bay 1. Developing the processing of cultivated products, 2. Provide training in stages. 3. Providing counseling in stages, 4. Optimizing existing production capacity, 5. Expanding the cultivation area, 6. Optimizing production, 7. Increasing access to capital, 8. Expand and maintain the marketing network.